Mejoramiento del arroz de secano para América Latina - Chatel, Marc; Guimarães, Elcio Perpétuo; Ospina, Yolima; Martínez Racines, César Pompilio; Borrero Correa, Jaime C. (International Center for Tropical Agriculture, 2010)
Improving upland rice for Latin America The ecosystems for upland rice in Latin America and the Caribbean and their limitations for rice cultivation are analyzed. The sites where the CIAT rice program and the collaborative project that the Center carries out with the French Agricultural Research Centre for International Development (CIRAD) evaluate and select genetic materials for upland conditions are also described, as well as the conventional genetic improvement activities carried out by CIAT since 1981 and those carried out by CIRAD since 1996. These activities include population development through population improvement and recurrent selection. The advances made so far are reported. As a result of these research projects, lines have been developed that present high yield potential and new commercial varieties have been released that have been quickly adopted by farmers. This has allowed the opening of new agricultural frontiers in Colombia’s Eastern Plains, and northern coast regions. In Brazil, the production of upland rice has been stimulated and, in Bolivia, alternatives to upland rice cultivation are being offered.